2008
DOI: 10.1093/eurheartj/ehn198
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative statin therapy on adverse postoperative outcomes in patients undergoing cardiac surgery: a meta-analysis of over 30 000 patients

Abstract: Our meta-analysis provides evidence that preoperative statin therapy exerts substantial clinical benefit on early postoperative adverse outcomes in cardiac surgery patients, but underscores the need for RCT trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(137 citation statements)
references
References 51 publications
9
119
1
8
Order By: Relevance
“…In a large meta-analysis (n = 31,725), preoperative statin exposure significantly reduced early mortality (OR = 0.57), stroke (OR = 0.74) and atrial fibrillation (OR = 0.6) after cardiac surgery [174]. In other study, which included 213,347 older patients who underwent major elective surgery, statin therapy was associated with 16% lower risk of AKI and 21% lower risk of mortality [175].…”
Section: Major Surgery and Statin Intolerancementioning
confidence: 95%
“…In a large meta-analysis (n = 31,725), preoperative statin exposure significantly reduced early mortality (OR = 0.57), stroke (OR = 0.74) and atrial fibrillation (OR = 0.6) after cardiac surgery [174]. In other study, which included 213,347 older patients who underwent major elective surgery, statin therapy was associated with 16% lower risk of AKI and 21% lower risk of mortality [175].…”
Section: Major Surgery and Statin Intolerancementioning
confidence: 95%
“…Atorvastatin is also considered to have a superior affinity for cardiac cellular membrane than pravastatin, since atorvastatin is a lipophilic statin whereas pravastatin is a hydrophilic statin. Clinical efficacy of statins in AF: Most of the randomized trials 8,33,34) and meta-analyses 9,35,36) in large-scale clinical studies have shown similar results with respect to the beneficial effica- Figure 1. Survival curve free from AF recurrence after upstream therapy with statins in patients on antiarrhythmic drugs.…”
Section: Discussionmentioning
confidence: 92%
“…[17] A subsequent Cochrane review that included 11 randomized trials in 984 participants undergoing (predominantly) CABG surgery [3] found that statins reduced the incidence of AF (OR: 0.40; 95% CI: 0.29-0.55) and led to a shorter intensive care unit (weighted mean difference, −3.39 [95% CI: −5.77 to −1.01] h) and hospital (weighted mean difference, −0.48 [95% CI: −0.85 to −0.11] days) stay, but no difference in mortality, MI, stroke or renal failure.…”
Section: The Evidence For Statinsmentioning
confidence: 99%